« The arrested step », Nightwood de Djuna Barnes : « Une image est une halte que fait l’esprit entre deux incertitudes » - Christiane Guillois (Revue LISA)
The tortured universe of Nightwood engages in a fundamental questioning of the common notion of man’s duality. Against a backdrop in which night is indistinguishable from day and characters are denied their wholeness, the body, essentially the body seen in movement, appears as the paradox inherent in the human condition. The reader encounters five characters drifting towards madness in an unsettled world, and a startlingly poetic prose that constantly disrupts the flow of events as it relentlessly explores their existential depths. With an unwavering sense of urgency, the literature of excess that defines Djuna Barnes’s work pushes back the limits of the unacceptable, as if to bring into the light that which is most intimate in man. She will have none of fossilized emotions and acts predicated on habit. She seeks the authentic, and it is this quest that leads her to bodies in motion, for while fashioned out of personal history, they throb with pulsations that are universal. In her search for the universal in this animal aspiring to transcendence and now passing through its human stage, she probes the bodies of her characters with a doggedness that leads to near-disintegration. What is human in man is not permanently established; it is to be rediscovered and reconquered, constantly.